Understanding material text cultures: a multidisciplinary view - Hilgert, Markus (Materiale Textkulturen, 2016)
The present volume comprises 6 highly original studies on material text cultures in different nontypographic societies stretching from the 3rd millennium cuneiform textual record of Ancient Mesopotamia to 20th century Qur'anic boards of northern and central African provenience. It provides a multidisciplinary approach to material text cultures complementary to the interdisciplinary, strongly theory-grounded research scheme of the CRC 933. Six research fellowships were awarded to outstanding young researchers for innovative, high-risk research proposals pertinent to the CRC 933's overall research scheme. Their studies contained in this volume add multidisciplinary dimension to material text culture research, satisfy the curiosity as to the applicability of the theoretical premises and methodology developed and tested by the CRC 933 to research on inscribed artefacts carried out on an international level and in different research environments and contribute to anchoring material text culture research as proposed by the CRC 933 within the tradition and broader context of other research strategies devoted to the material dimension of writing, such as the filologia materiale
Erscheint als Open Access bei De Gruyter
Keywords: Aufsatzsammlung; Geschichte; Materialität; Text; Schriftlichkeit